Forgotten Grasslands of the South Natural History and Conservation - Noss, Reed F.; SpringerLink (Online service) (Washington, DC : Island Press/Center for Resource Economics : Imprint: Island Press, 2013)
Forgotten Grasslands of the South is a literary and scientific case study of some of the biologically richest and most endangered ecosystems in North America. Eminent ecologist Reed Noss tells the story of how southern grasslands arose and persisted over time and addresses questions that are fundamental for conserving these vital yet poorly understood ecosystems. The author examines the natural history of southern grasslands their origin and history (geologic, vegetation, and human) biological hotspots and endangered ecosystems physical determinants of grassland distribution, including ecology, soils, landform, and hydrology fire, herbivores, and ecological interactions The final chapter presents a general conservation strategy for southern grasslands, including prioritization, protection, restoration, and management. Also included are examples of ongoing restoration projects, along with a prognosis for the future. In addition to offering fascinating new information about these little-studied ecosystems, Noss demonstrates how natural history is central to the practice of conservation. Natural history has been on a declining trajectory for decades, as theory and experimentation have dominated the field of ecology. Ecologists are coming to realize that these divergent approaches are in fact complementary, and that pursuing them together can bring greater knowledge and understanding of how the natural world works and how we can best conserve it. Forgotten Grasslands of the South explores the overarching importance of ecological processes in maintaining healthy ecosystems, and is the first book of its kind to apply natural history, in a modern, comprehensive sense, to the conservation of biodiversity across a broad region. It sets a new standard for scientific literature and is essential reading not only for those who study and work to conserve the grasslands of the South but also for everyone who is fascinated by the natural world.
Foreword; Edward O. Wilson -- Preface -- Acknowledgments -- 1. Natural History of a Forgotten American Grassland. Natural History for Conservation. Grasslands in the South? What and Where Are Southern Grasslands? The Grasslands Considered in This Book. Joshua Creek -- 2. Origin and History. A General Model. Geology, Physiography, and Pre-Neogene History. Neogene and Quaternary History. Disjunctions and the Gulf Coastal Corridor. Human History in the South, as It Relates to Grasslands. Mills Creek -- 3. Biological Hotspots and Endangered Ecosystems. Discovering Lost Worlds. Endemism. Centers of Endemism in the South. Peripherals and Disjuncts. Species Richness. Species Richness in Southern Grasslands. People Care about Diversity, Endemism, and Disjunctions. The Decline of Southern Grasslands -- 4. Physical Factors: Rock, Soil, Landform, Water, and Wind. The Purpose of My Journeys. Rock, Soil, and Landform. Water. Wind, Storms, and Sea-Level Rise -- 5. Fire, Big Animals, and Interactions. Bottom-Up, Top-Down, and Sideways. Fire. Herbivores. Interaction of Fire and Hydrology. The Enigmatic Canebrakes -- 6. The Future of Southern Grasslands: Outline of a Strategy. A Conservation Strategy for Southern Grasslands. Examples of Restoration Projects. The Future? -- Species List -- Literature Cited -- About the Author -- Index.
Keywords: Environmental sciences; Ecology; Trees; Wildlife management; Nature Conservation; Environment; Environment, general; Nature Conservation; Fish & Wildlife Biology & Management; Ecology; Terrestial Ecology; Tree Biology